Relationship Levels of Osh Knowledge Towards Discipline of Workers in The Time of The Covid-19 Pandemic Dolly Bird Market Project Surabaya - Achmad Marzuki Ferdianto; Diah Ayu Restuti Wulandari (NAROTAMA UNIVERSITY, Indonesia, 2022)
The COVID-19 pandemic has weakened various sectors in Indonesia, including the construction sector. This fast-transmitting virus raises the potential for contracting workers in the field, which is defined as an occupational disease. One of the protective behaviors for contracting the virus is the discipline of workers in obeying health protocols, especially the discipline of wearing masks as one of the work safety PPE. This study aims to determine the relationship between the level of knowledge of occupational safety and health (K3) on worker discipline in wearing masks at the Dolly Bird Market Surabaya development project. This research is a descriptive analytic study with a cross sectional approach. The sample in this study was 33 workers and research subjects were selected using random sampling technique. The statistical test used to analyze the research data is a simple linear regression coefficient with the SPSS 26 program. The results of the analysis of the relationship between the level of knowledge of occupational safety and health (K3) on worker discipline in wearing masks using the regression coefficient test obtained a value of 0.028 which states that the effect variable X to Y is positive. From the results of the T test, it is found that Tcount > Ttable, thus Ho is rejected and Ha is accepted, so there is a relationship between the level of K3 knowledge and the discipline of wearing masks on the construction project workers of the Surabaya Dolly Bird Market.